Correction: Concentration-induced structural transition of block polymer self-assemblies on a nanoparticle surface: computer simulation. Issue 109 (10th November 2016) - Xiang, Wenjun; Zhu, Zhaoju; Song, Xianyu; Zhong, Cheng; Wang, Chengjie; Ma, Yongzhang
Abstract : Correction for 'Concentration-induced structural transition of block polymer self-assemblies on a nanoparticle surface: computer simulation' by Wenjun Xiang et al., RSC Adv., 2016, 6, 102057–102067